Factors associated with acute oral mucosal reaction induced by radiotherapy in head and neck squamous cell carcinoma: A retrospective single-center experience. Issue 50 (December 2017) - Tao, Zhenchao; Gao, Jin; Qian, Liting; Huang, Yifan; Zhou, Yan; Yang, Liping; He, Jian; Yang, Jing; Wang, Ru; Zhang, Yangyang
Abstract : Abstract: To investigate risk factors for acute oral mucosal reaction during head and neck squamous cell carcinoma radiotherapy. A retrospective study of patients with head and neck squamous cell carcinoma who underwent radiotherapy from November 2013 to May 2016 in Anhui Provincial Cancer Hospital was conducted. Data on the occurrence and severity of acute oral mucositis were extracted from clinical records. Based on the Radiation Therapy Oncology Group (RTOG) grading of acute radiation mucosal injury, the patients were assigned into acute reaction (grades 2–4) and minimum reaction (grades 0–1) groups. Preradiotherapy characteristics and treatment factors were compared between the 2 groups. Multivariate logistic regression analysis was used to detect the independent factors associated with acute oral mucosal reactions. Eighty patients completed radiotherapy during the study period. Oral mucosal reactions were recorded as 25, 31, and 24 cases of grades 1, 2, and 3 injuries, respectively. Significant differences between acute reaction and minimum reaction groups were detected in cancer lymph node (N) staging, smoking and diabetes history, pretreatment platelet count and T-Helper/T-Suppressor lymphocyte (Th/Ts) ratio, concurrent chemotherapy, and total and single irradiation doses. Multivariate analysis showed that N stage, smoking history, single dose parapharyngeal irradiation, and pretreatment platelet count were independent risk factors for acute radiation induced oral mucosal reaction. Smoking history, higher grading of N stage, higher single dose irradiation, and lower preirradiation platelet count may increase the risk and severity of acute radiation oral mucosal reaction in radiotherapy of head and neck cancer patients.